Rodriguez, José Rodrigo (2013). Como decidem as cortes? Para uma crítica do direito (brasileiro) - Rio de Janeiro: FGV - de Souza, Matheus Barra (Direito.UnB - Revista de Direito da Universidade de Brasília, 2019)